Sustainable Community Development: A Case Study of Xang Hai Village, Pak Ou District, Luang Prabang Province - SENGPHACHANH, Bouasavanh; VONHVILAI, Xaiyaphone; PHONESALY , Naunseng (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The research aims to: 1) Study the overall context of the community, analyze the community development plan for a sustainable community, and 2) The physical potential, resource potential of the community and plan a physical development plan to promote tourism in accordance with the current situation. The research methods used in this study were data from documents, field surveys, observations, interviews and analysis of results. The target groups used in the study were government officials, village heads, residents, tourism business operators and tourists during the year 2023-2024. The data analysis was conducted to find areas in the community that have potential for development to reflect culture, customs and architectural styles that can promote tourism activities. The study found that 1) The overall context of the community, analyzing the community development plan for a sustainable community, found that there was a lack of physical planning to promote tourism and good living. From the past community development, there have been attempts to create a community-based tourism network, with a focus on social and economic development as the main focus, but there was a lack of systematic physical development planning to promote tourism to achieve more effective results; 2) The physical potential, resource potential of the community and the planning of physical development plans to promote tourism to suit the current situation. It is seen that there are many cultural heritages and local wisdoms that are worth preserving and spreading, such as cultural values, lifestyles, embroidery, etc. These things can be applied by the community to add economic value to the community. However, the previous form of community tourism only emphasized that tourists come to see and experience the superficial lifestyle, but did not bring the knowledge content that is the real lifestyle and culture of the community to communicate to tourists so that they can recognize and experience it.